Downward-blowing water-cooling PE film functional material as well as preparation method and application thereof
Through the combination of ZnMgAl-MOFs, nano-minerals and biological antibacterial agents, the problems of molecular chain entanglement and interlayer adhesion of downward-blown water-cooled PE film were solved, achieving a soft feel and the function of locking in the freshness of fruits and vegetables, thereby improving the bag-making efficiency and the preservation effect of fruits and vegetables.
Patent Information
- Application Number
- CN202510706076.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-10-10
AI Technical Summary
The rapid cooling process of downward-blown water-cooled PE film causes increased molecular chain entanglement density and interlayer adhesion problems, which affect the bag-making efficiency and fruit and vegetable packaging effect.
By combining ZnMgAl-MOFs, nano-minerals and biological antibacterial agents, a "sandwich" structure with selective permeability is constructed through step-by-step microwave crystallization and ultrasonic intercalation processes, forming a synergistic antibacterial-adsorption network, maintaining a soft feel and improving anti-adhesion effects.
It achieves the soft feel and excellent anti-adhesion effect of PE film, and at the same time has the function of locking the freshness of fruits and vegetables. It can maintain a low-oxygen and high-carbon dioxide atmosphere in the sealed packaging bag, thereby improving the preservation effect of fruits and vegetables.
Smart Images

Figure CN120758051A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer material processing, in particular to a downward-blowing water-cooled PE film functional material and a preparation method and application thereof. Background Art
[0002] Downward-blown, water-cooled PE film exhibits excellent transparency and flexibility due to its rapid cooling, which inhibits crystallization. However, even with a high proportion of lubricant added to the opening, serious interlayer adhesion issues can occur, severely impacting the efficiency of subsequent bag-making processes and hindering the opening of bags for fruit and vegetable packaging. Rapid cooling can increase the density of PE molecular chains by 2-3 times, and excessive addition of lubricant can increase film rigidity, contradicting the intended softness achieved by this process. Summary of the Invention
[0003] The purpose of the present invention is to solve the problems existing in the prior art, thereby providing a downward-blowing water-cooled PE film functional material and its preparation method and application. The PE film prepared using the downward-blowing water-cooled PE film functional material has excellent anti-adhesion effect while ensuring the soft feel of the PE film, and also has the function of locking the freshness of fruits and vegetables, and has broad application prospects. In addition, the preparation method of the downward-blowing water-cooled PE film functional material is simple and convenient.
[0004] In order to achieve the above objectives, in a first aspect, the present invention provides a downward-blowing water-cooled PE film functional material, wherein the film functional material contains ZnMgAl-MOFs, nano-minerals and a biological antibacterial agent; wherein,
[0005] The nano mineral is nano kaolin and / or nano montmorillonite;
[0006] The biological antibacterial agent is ε-polylysine.
[0007] Preferably, the ZnMgAl-MOFs are synthesized using a step-by-step microwave crystallization process.
[0008] Preferably, the ZnMgAl-MOFs are modified by a surfactant.
[0009] More preferably, the surfactant is sodium dodecylbenzenesulfonate and / or cetyltrimethylammonium bromide.
[0010] In a second aspect, the present invention provides a method for preparing a downward-blowing water-cooled PE film functional material, characterized in that the preparation method comprises:
[0011] 1) dispersing the nano-minerals in an acetic acid solution containing a biological antibacterial agent, and ultrasonically exfoliating the nano-minerals to obtain a colloidal dispersion;
[0012] 2) adding the ZnMgAl-MOFs solution to the colloidal dispersion and dispersing the solution by ultrasonication;
[0013] 3) During the crystallization process of the MOFs material, a surfactant is added to continue the microwave solvent thermal reaction, and the product is collected by centrifugation, washed, and dried.
[0014] Preferably, in step 1), the nano mineral is nano kaolin and / or nano montmorillonite.
[0015] Preferably, the biological antibacterial agent is ε-polylysine.
[0016] More preferably, the mass ratio of the nano-mineral to the biological antibacterial agent is 1:0.1-0.5.
[0017] Preferably, in step 1), the conditions for ultrasonic peeling include: time of 10-30 min, temperature of 50-70° C., and ultrasonic power of 200-400 W.
[0018] Preferably, in step 2), the ZnMgAl-MOFs solution is an aqueous solution with a mass concentration of 1-5 g / L.
[0019] Preferably, in step 2), the ultrasonic dispersion conditions include: ultrasonic frequency of 25-30kHz, power density of 0.5W / cm 3 , time is 20-40min.
[0020] Preferably, in step 2), the preparation method of the ZnMgAl-MOFs comprises:
[0021] a) dissolving zinc salt, magnesium salt and aluminum salt in a solvent to obtain a mixed solution, adding a ligand solution to the mixed solution, and performing a microwave solvothermal reaction to obtain a MOFs material;
[0022] b) adding a surfactant during the first crystallization process of the MOFs material to continue the microwave solvothermal reaction to obtain ZnMgAl-MOFs;
[0023] Preferably, in step a), the zinc salt is selected from one or two or more of zinc nitrate, zinc chloride and zinc sulfate, the magnesium salt is selected from one or two or more of magnesium nitrate, magnesium chloride and magnesium sulfate, and the aluminum salt is selected from one or two or more of aluminum nitrate, aluminum chloride and aluminum sulfate.
[0024] Preferably, the ligand solution is an ethanol solution of 2-methylimidazole and trimesic acid.
[0025] More preferably, in step a), the molar ratio of the zinc salt, the magnesium salt and the aluminum salt is 1:0.5-2:0.5-2, wherein the zinc salt is calculated as zinc ion, the magnesium salt is calculated as magnesium ion, and the aluminum salt is calculated as aluminum ion.
[0026] Further preferably, in step a), the conditions of the microwave solvothermal reaction include: power of 800-1200W, temperature of 140-150°C, and time of 20-40min.
[0027] More preferably, in step b), the surfactant is sodium dodecylbenzenesulfonate and / or cetyltrimethylammonium bromide.
[0028] More preferably, the concentration of the surfactant is 0.01-0.05 mol / L.
[0029] More preferably, in step b), the conditions of the microwave solvothermal reaction include: power of 800-1200W, temperature of 140-150°C, and time of 20-40min.
[0030] Preferably, in step 3), the surfactant is sodium dodecylbenzenesulfonate and / or cetyltrimethylammonium bromide.
[0031] Preferably, the concentration of the surfactant is 0.01-0.05 mol / L.
[0032] Preferably, in step 3), the conditions of the microwave solvothermal reaction include: power of 800-1200W, temperature of 140-150°C, and time of 20-40min.
[0033] In a third aspect, the present invention provides a downward-blowing water-cooled PE film, characterized in that the downward-blowing water-cooled PE film comprises a functional material, a PE resin and maleic anhydride grafted PE; wherein the functional material is the downward-blowing water-cooled PE film functional material described in the first aspect or the downward-blowing water-cooled PE film functional material prepared by the preparation method described in the second aspect.
[0034] In this technical solution, the present invention first synthesizes the ZnMgAl-MOFs framework through a step-by-step microwave crystallization process, and then ultrasonically intercalates the resulting material into a functional, down-blown, water-cooled PE film with excellent anti-adhesive properties. By combining microwave dynamic crystallization with ultrasonic intercalation, a selectively permeable "sandwich" structure (MOFs layer / mineral layer / polymer matrix) is constructed through valence gradient design and mineral intercalation. This creates a synergistic antibacterial-adsorption network while maintaining the soft feel of the down-blown, water-cooled PE film and achieving excellent anti-adhesive properties.
[0035] In the first stage, a Zn-Mg-Al core-shell structure is formed, in which Zn2+ Preferentially coordinates with 2-methylimidazole to form a ZIF-8 similar structure, Al 3+ By [Al(OH)6] 3 -octahedron and trimesic acid construct secondary structural units; 2-methylimidazole and trimesic acid dual ligands are used to collaboratively construct a three-dimensional skeleton, and sodium dodecylbenzenesulfonate and hexadecyltrimethylammonium bromide are introduced during the crystallization process of the MOFs basic framework to collaboratively modify the internal pores of MOFs, inhibiting grain growth and optimizing the adsorption sites of MOFs for ethylene while maintaining the particle size of the ZnMgAl-MOFs basic framework; in the ZnMgAl-MOFs basic framework, gradient redox sites are formed by the difference in metal ion valence states, among which Zn 2+ As the antibacterial active center, it destroys the microbial cell membrane through the contact sterilization mechanism; Mg 2+ As an electron transfer medium, Zn 2+ The sustained release stability and the skeleton stability of MOFs materials; Al 3+ The chemical adsorption of ethylene molecules is enhanced through Lewis acid sites. Ultrasonic cavitation is then used to drive nano-kaolin and nano-montmorillonite into the MOFs pores, promoting electrostatic bonding between the nano-minerals and the MOFs pores, filling the gaps in the MOFs framework to form a layered and multi-level porous structure, further improving the MOFs' anti-adhesion properties, ethylene adsorption properties, and spontaneous gas-conditioning capabilities. At the same time, organic / biological antimicrobial agents are stabilized in MOFs through coordination bonding, allowing for a gradual, sustained release in practical applications to further enhance the antimicrobial effect.
[0036] The PE film prepared using the downward-blown water-cooled PE film of the present invention, which contains functional materials, has excellent anti-adhesion effect and excellent antibacterial effect. In addition, the PE film constructs a gas-selective transmission channel with the help of mineral intercalation and has good spontaneous gas-conditioning function. After being made into a sealed packaging bag, it can maintain a low-oxygen and high-carbon dioxide gas atmosphere in the bag. The gas permeability is more in line with the breathing requirements of fruits and vegetables, and is more conducive to locking the freshness of fruits and vegetables.
[0037] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following detailed description, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:
[0039] Figure 1 This is a TEM image of the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1 of the present invention;
[0040] Figure 2This is an SEM image of a PE film made using the downward-blowing water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1 of Application Example 1 of the present invention;
[0041] Figure 3 This is a record of the appearance changes of pearl white guava during the experimental process of Test Example 6 of the present invention;
[0042] Figure 4 This is a graph showing the changing trends of various indicators of pearl white guava during the experimental process of detection example 6 of the present invention. DETAILED DESCRIPTION
[0043] The following is a detailed description of the specific embodiments of the present invention. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.
[0044] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0045] In a first aspect, the present invention provides a downward-blowing water-cooled PE film functional material, wherein the film functional material contains ZnMgAl-MOFs, nano-minerals and a biological antibacterial agent; wherein,
[0046] The nano mineral is nano kaolin and / or nano montmorillonite;
[0047] The biological antibacterial agent is ε-polylysine.
[0048] The downward-blowing water-cooled PE film functional material of the present invention has a Zn-Mg-Al core-shell structure, wherein Zn 2+ Preferentially coordinates with 2-methylimidazole to form a ZIF-8 similar structure, Al 3+ By [Al(OH)6] 3 -octahedron and trimesic acid construct secondary structural units; 2-methylimidazole and trimesic acid dual ligands are used to collaboratively construct a three-dimensional skeleton, and sodium dodecylbenzenesulfonate and hexadecyltrimethylammonium bromide are introduced during the crystallization process of the MOFs basic framework to collaboratively modify the internal pores of MOFs, inhibiting grain growth and optimizing the adsorption sites of MOFs for ethylene while maintaining the particle size of the ZnMgAl-MOFs basic framework; in the ZnMgAl-MOFs basic framework, gradient redox sites are formed by the difference in metal ion valence states, among which Zn 2+As the antibacterial active center, it destroys the microbial cell membrane through the contact sterilization mechanism; Mg 2+ As an electron transfer medium, Zn 2+ The sustained release stability and the skeleton stability of MOFs materials; Al 3+ The chemical adsorption of ethylene molecules is enhanced through Lewis acid sites. Ultrasonic cavitation is then used to drive nano-kaolin and nano-montmorillonite into the MOFs pores, promoting electrostatic bonding between the nano-minerals and the MOFs pores, filling the gaps in the MOFs framework to form a layered and multi-level porous structure, further improving the MOFs' anti-adhesion properties, ethylene adsorption properties, and spontaneous gas-conditioning capabilities. At the same time, organic / biological antimicrobial agents are stabilized in MOFs through coordination bonding, allowing for a gradual, sustained release in practical applications to further enhance the antimicrobial effect.
[0049] In a preferred embodiment of the present invention, the ZnMgAl-MOFs are synthesized using a step-by-step microwave crystallization process.
[0050] In a preferred embodiment of the present invention, the ZnMgAl-MOFs are modified by a surfactant.
[0051] In a preferred embodiment of the present invention, the surfactant is sodium dodecylbenzenesulfonate and / or cetyltrimethylammonium bromide.
[0052] In a second aspect, the present invention provides a method for preparing a downward-blowing water-cooled PE film functional material, characterized in that the preparation method comprises:
[0053] 1) dispersing the nano-minerals in an acetic acid solution containing a biological antibacterial agent, and ultrasonically exfoliating the nano-minerals to obtain a colloidal dispersion;
[0054] 2) adding the ZnMgAl-MOFs solution to the colloidal dispersion and dispersing the solution by ultrasonication;
[0055] 3) During the crystallization process of the MOFs material, a surfactant is added to continue the microwave solvent thermal reaction, and the product is collected by centrifugation, washed, and dried.
[0056] The present invention first synthesizes the ZnMgAl-MOFs framework through a step-by-step microwave crystallization process, followed by ultrasonic intercalation to create a functional material for a downward-blown water-cooled PE film with excellent anti-adhesion properties. By combining microwave dynamic crystallization with ultrasonic intercalation, a valence gradient design and mineral intercalation are employed to construct a "sandwich" structure (MOFs layer / mineral layer / polymer matrix) with selective permeability, forming a synergistic antibacterial-adsorption network while maintaining the soft feel of the downward-blown water-cooled PE film and achieving excellent anti-adhesion properties.
[0057] In a preferred embodiment of the present invention, in step 1), the nano mineral is nano kaolin and / or nano montmorillonite.
[0058] In a preferred embodiment of the present invention, the biological antibacterial agent is ε-polylysine.
[0059] In a preferred embodiment of the present invention, the mass ratio of the nano-mineral to the biological antibacterial agent is 1:0.1-0.5.
[0060] In a preferred embodiment of the present invention, in step 1), the conditions for ultrasonic peeling include: time of 10-30 min, temperature of 50-70° C., and ultrasonic power of 200-400 W.
[0061] In a preferred embodiment of the present invention, in step 2), the ZnMgAl-MOFs solution is an aqueous solution with a mass concentration of 1-5 g / L.
[0062] In a preferred embodiment of the present invention, in step 2), the conditions for ultrasonic dispersion include: ultrasonic frequency of 25-30 kHz, power density of 0.5 W / cm 3 , time is 20-40min.
[0063] In a preferred embodiment of the present invention, in step 2), the preparation method of the ZnMgAl-MOFs comprises:
[0064] a) dissolving zinc salt, magnesium salt and aluminum salt in a solvent to obtain a mixed solution, adding a ligand solution to the mixed solution, and performing a microwave solvothermal reaction to obtain a MOFs material;
[0065] b) adding a surfactant during the first crystallization process of the MOFs material to continue the microwave solvothermal reaction to obtain ZnMgAl-MOFs;
[0066] In a preferred embodiment of the present invention, in step a), the zinc salt is selected from one or two or more of zinc nitrate, zinc chloride and zinc sulfate, the magnesium salt is selected from one or two or more of magnesium nitrate, magnesium chloride and magnesium sulfate, and the aluminum salt is selected from one or two or more of aluminum nitrate, aluminum chloride and aluminum sulfate.
[0067] In a preferred embodiment of the present invention, the ligand solution is an ethanol solution of 2-methylimidazole and trimesic acid.
[0068] In a preferred embodiment of the present invention, in step a), the ratio of the zinc salt, the magnesium salt and the aluminum salt is 1:0.5-2:0.5-2, wherein the zinc salt is calculated as zinc ion, the magnesium salt is calculated as magnesium ion, and the aluminum salt is calculated as aluminum ion.
[0069] In a preferred embodiment of the present invention, in step a), the conditions of the microwave solvothermal reaction include: power of 800-1200W, temperature of 140-150°C, and time of 20-40 min.
[0070] In a preferred embodiment of the present invention, in step b), the surfactant is sodium dodecylbenzenesulfonate and / or cetyltrimethylammonium bromide.
[0071] In a preferred embodiment of the present invention, the concentration of the surfactant is 0.01-0.05 mol / L.
[0072] In a preferred embodiment of the present invention, in step b), the conditions of the microwave solvothermal reaction include: power of 800-1200W, temperature of 140-150°C, and time of 20-40 min.
[0073] In a preferred embodiment of the present invention, in step 3), the surfactant is sodium dodecylbenzenesulfonate and / or cetyltrimethylammonium bromide.
[0074] In a preferred embodiment of the present invention, the concentration of the surfactant is 0.01-0.05 mol / L.
[0075] In a preferred embodiment of the present invention, in step 3), the conditions of the microwave solvothermal reaction include: power of 800-1200W, temperature of 140-150°C, and time of 20-40min.
[0076] In a preferred embodiment of the present invention, the washing conditions include washing with ethanol three times.
[0077] In a preferred embodiment of the present invention, the drying conditions include vacuum drying at 105°C.
[0078] In a third aspect, the present invention provides a downward-blowing water-cooled PE film, characterized in that the downward-blowing water-cooled PE film comprises a functional material, a PE resin and maleic anhydride grafted PE; wherein the functional material is the downward-blowing water-cooled PE film functional material described in the first aspect or the downward-blowing water-cooled PE film functional material prepared by the preparation method described in the second aspect.
[0079] The PE film prepared using the downward-blown water-cooled PE film of the present invention, which contains functional materials, has excellent anti-adhesion effect and excellent antibacterial effect. In addition, the PE film constructs a gas-selective transmission channel with the help of mineral intercalation and has good spontaneous gas-conditioning function. After being made into a sealed packaging bag, it can maintain a low-oxygen and high-carbon dioxide gas atmosphere in the bag. The gas permeability is more in line with the breathing requirements of fruits and vegetables, which is more conducive to locking the freshness of fruits and vegetables.
[0080] The present invention will be described in detail below by way of examples. In the following examples, the drugs and pharmaceuticals are all conventional commercial products.
[0081] Example 1
[0082] (1) Dissolve 1 mmol of 2-methylimidazole and 1 mmol of trimesic acid in 10 ml of ethanol to obtain a ligand solution;
[0083] (2) 1 mmol zinc nitrate, 1 mmol magnesium nitrate, and 1 mmol aluminum nitrate were dissolved in 10 ml deionized water to obtain a mixed solution. The ligand solution was added to the mixed solution, and the mixture was subjected to microwave solvothermal reaction at a power of 1000 W and a temperature of 145°C for 30 min.
[0084] (3) During the first crystallization of the MOFs material, 1 mmol of sodium dodecylbenzenesulfonate and 1 mmol of hexadecyltrimethylammonium bromide were added and the microwave solvent thermal reaction was continued for 30 min to obtain ZnMgAl-MOFs;
[0085] (4) 0.1 g of nano-kaolin and 0.1 g of nano-montmorillonite were dispersed in an acetic acid solution containing 0.01 g of ε-polylysine, and ultrasonically stripped at 60°C to obtain a colloidal dispersion;
[0086] (5) The ZnMgAl-MOFs solution was added to the colloidal dispersion and ultrasonicated at a frequency of 28 kHz and a power density of 0.5 W / cm 3 During the crystallization process of MOFs materials, 1 mmol of sodium dodecylbenzenesulfonate and 1 mmol of hexadecyltrimethylammonium bromide were added to continue the microwave solvent thermal reaction to inhibit excessive grain growth and maintain the nanometer size of MOFs materials.
[0087] (6) After the product was collected by centrifugation, it was washed with ethanol three times and dried in vacuo at 105 °C to obtain a downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs, which was recorded as A1.
[0088] Depend on Figure 1 The TEM image of the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs shows that the nano-minerals are successfully compounded in the microporous channels and surface of ZnMgAl-MOFs, indicating the successful synthesis of the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs.
[0089] Example 2
[0090] The method of Example 1 was followed, except that the zinc nitrate in step (1) was replaced by zinc sulfate, the magnesium nitrate was replaced by magnesium sulfate, and the aluminum nitrate was replaced by aluminum chloride. Other conditions remained unchanged, to obtain a downward-blowing water-cooled PE film functional material containing ZnMgAl-MOFs, which was recorded as A2.
[0091] Example 3
[0092] The method of Example 1 was followed, except that the power of 1000W in step (2) was replaced by a power of 800W, and other conditions remained unchanged, to obtain a downward-blowing water-cooled PE film functional material containing ZnMgAl-MOFs, which was recorded as A3.
[0093] Application Example 1
[0094] The ZnMgAl-MOFs-containing downward-blown water-cooled PE film functional material, PE resin, and maleic anhydride-grafted PE prepared in Example 1 were blended and granulated by a twin-screw extruder to obtain a downward-blown water-cooled PE film functional masterbatch; the functional masterbatch and PE resin were blown into a downward-blown water-cooled film blowing machine to obtain a downward-blown water-cooled PE film.
[0095] Depend on Figure 2 Application Example 1 From the SEM image of the PE film prepared using the downward-blowing water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1, it can be seen that the downward-blowing water-cooled PE film prepared using the downward-blowing water-cooled PE film functional material containing ZnMgAl-MOFs of the present invention has a porous structure, and the film is rough and dense, which provides a guarantee for excellent anti-adhesion properties. It can also be seen that the downward-blowing water-cooled PE film functional material containing ZnMgAl-MOFs of the present invention is effectively dispersed in the downward-blowing film.
[0096] Test Example 1
[0097] Test Application Example 1: The strength of a plastic film (referred to as MOFs film) made from the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1 and an ordinary downward-blown water-cooled PE film (referred to as ordinary PE) on the market were tested. The test method referred to GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets". The test results are shown in Table 1.
[0098] Table 1
[0099]
[0100] It can be seen from the data in Table 1 that the plastic film made from the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1 in Application Example 1 of the present invention has better tensile strength than the ordinary downward-blown water-cooled PE film on the market.
[0101] Test Example 2
[0102] Test Application Example 1 The anti-adhesion performance of the plastic film (referred to as MOFs film) made from the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1 and the ordinary downward-blown water-cooled PE film on the market (referred to as ordinary PE) was tested. The test method referred to GB / T 10006-2021 "Determination of the friction coefficient of plastic films and sheets". The test results are shown in Table 2.
[0103] Table 2
[0104] Static friction coefficient Dynamic friction coefficient MOFs thin films 0.356 0.378 Ordinary PE 0.383 1.069
[0105] Test Example 3
[0106] Test Application Example 1: The anti-adhesion performance of a plastic film (referred to as MOFs film) made from the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1 and an ordinary downward-blown water-cooled PE film on the market (referred to as ordinary PE) was tested. The test method referred to the ASTM D3354 parallel plate method to measure the adhesion load of the plastic film. The test results are shown in Table 3.
[0107] Table 3
[0108] Peel force (N / cm) MOFs thin films 0.4 Ordinary PE 0.8
[0109] It can be seen from the data in Tables 2 and 3 that the plastic film made from the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1 in Application Example 1 of the present invention has better anti-adhesion performance than the ordinary downward-blown water-cooled PE film on the market.
[0110] Test Example 4
[0111] Test Application Example 1 The antibacterial properties of a plastic film (referred to as MOFs film) made from the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1 and an ordinary downward-blown water-cooled PE film on the market (referred to as ordinary PE) were tested. The test method referred to GB / T 31402-2023 "Determination of antibacterial activity on the surface of plastics and other non-porous materials". The test results are shown in Table 4.
[0112] Table 4
[0113] Escherichia coli inhibition rate (%) Staphylococcus aureus inhibition rate (%) MOFs thin films 99.99 99.99 Ordinary PE 0.67 0.33
[0114] It can be seen from the data in Table 4 that the antibacterial performance of the plastic film made from the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1 in Application Example 1 of the present invention is much higher than the antibacterial performance of ordinary downward-blown water-cooled PE films on the market, indicating that the MOFs film of the present invention has better antibacterial performance.
[0115] Test Example 5
[0116] Test Application Example 1 The ethylene adsorption rate of a plastic film (referred to as MOFs film) and an ordinary blank PE film (referred to as ordinary PE) made of the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1 was tested. The test method was carried out in a 3.9L glass box with reference to GB21551.4-2024 "Antibacterial, sterilization and purification functions of household and similar electrical appliances". The results are shown in Table 5.
[0117] Table 5
[0118] Ethylene adsorption rate (%) MOFs thin films 68.63 Ordinary PE 5.66
[0119] From the data in Table 5, it can be seen that the ethylene adsorption rate of the plastic film made from the downward-blown water-cooled PE film functional material containing ZnMgAl-MOFs prepared in Example 1 in Application Example 1 of the present invention is much higher than the ethylene adsorption rate of ordinary downward-blown water-cooled PE films on the market, indicating that the MOFs film of the present invention has better preservation ability.
[0120] Test Example 6
[0121] The specific method for determining the freshness-locking performance of pearl white guava is as follows:
[0122] (1) A plastic film made from the ZnMgAl-MOFs-containing downward-blown water-cooled PE film functional material prepared in Example 1 (hereinafter referred to as MOFs film) and an ordinary blank PE film (hereinafter referred to as ordinary PE) were prepared into 35×25 cm packaging bags;
[0123] (2) Pearl white guavas with consistent maturity, no mechanical damage, no decay, and similar specifications were selected; MOFs film and ordinary PE were divided into 10 groups, with 3 catties of guavas in each group. After packaging, each group of guavas was guaranteed to have the same air volume. The guavas were sealed and stored in an environment with a temperature of 25°C and a relative humidity of 60%. Every two days, photos were taken to record the appearance of the guavas. The weight loss rate, Vc content, soluble solid content, O2 / CO2 volume fraction in the bag, peroxidase (POD) content, and polyphenol oxidase (PPO) content of the guavas were measured. The results are shown in Table 6 and Table 6. Figure 3-Figure 4 shown.
[0124] Wherein, weight loss rate determination: the weight of the perfume lemon was measured using a balance, and the weight loss rate was calculated by the difference between the weight before and after, weight loss rate = (initial weight - measured weight) / initial weight × 100%;
[0125] Determination of Vitamin C content: Referring to GB 5009.86-2016 "National Food Safety Standard - Determination of Ascorbic Acid in Foods", the Vitamin C content was determined by the third method 2,6-dichloroindophenol titration method, and the test was repeated three times;
[0126] Determination of soluble solids content: Use a portable digital refractometer.
[0127] O2 / CO2 volume fraction measurement: Use a portable O2 / CO2 meter to measure the gas volume fraction in the package;
[0128] Peroxidase (POD) content determination: The peroxidase content was determined by spectrophotometry;
[0129] Polyphenol oxidase (PPO) content was determined by spectrophotometry.
[0130] Table 6
[0131]
[0132]
[0133] From the data in Table 6 and Figure 3-Figure 4 It can be seen from the content that the various indicators obtained by using the MOFs film of the present invention to preserve pearl white guava are better than the preservation ability of ordinary PE film on the market for pearl white guava, indicating that the MOFs film of the present invention can better retain the moisture and nutrients of pearl white guava and delay the corruption of pearl white guava.
[0134] In summary, the PE film prepared by the downward-blowing water-cooled PE film functional material containing ZnMgAl-MOFs of the present invention has excellent anti-adhesion effect while ensuring the soft feel of the PE film, and also has the function of locking the freshness of fruits and vegetables, and has broad application prospects. In addition, the preparation method of the downward-blowing water-cooled PE film functional material is simple and convenient.
[0135] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the scope of protection of the present invention.
[0136] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any appropriate manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0137] In addition, the various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A downward-blowing water-cooled PE film functional material, characterized in that: The thin film functional material contains ZnMgAl-MOFs, nano minerals and biological antibacterial agents; wherein, The nano mineral is nano kaolin and / or nano montmorillonite; The biological antibacterial agent is ε-polylysine.
2. The downward-blowing water-cooled PE film functional material according to claim 1, characterized in that: The ZnMgAl-MOFs are synthesized using a step-by-step microwave crystallization process; Preferably, the ZnMgAl-MOFs are modified by a surfactant; More preferably, the surfactant is sodium dodecylbenzenesulfonate and / or cetyltrimethylammonium bromide.
3. A method for preparing a downward-blowing water-cooled PE film functional material, characterized in that: The preparation method comprises: 1) dispersing the nano-minerals in an acetic acid solution containing a biological antibacterial agent, and ultrasonically exfoliating the nano-minerals to obtain a colloidal dispersion; 2) adding the ZnMgAl-MOFs solution to the colloidal dispersion and dispersing the solution by ultrasonication; 3) During the crystallization process of the MOFs material, a surfactant is added to continue the microwave solvent thermal reaction, and the product is collected by centrifugation, washed, and dried.
4. The preparation method according to claim 3, characterized in that In step 1), the nano mineral is nano kaolin and / or nano montmorillonite; Preferably, the bioantimicrobial agent is ε-polylysine; More preferably, the mass ratio of the nano-mineral to the biological antibacterial agent is 1:0.1-0.
5.
5. The preparation method according to claim 3 or 4, characterized in that In step 1), the conditions for ultrasonic peeling include: time of 10-30 min, temperature of 50-70° C., and ultrasonic power of 200-400 W.
6. The preparation method according to any one of claims 3 to 5, characterized in that In step 2), the ZnMgAl-MOFs solution is an aqueous solution with a mass concentration of 1-5 g / L; Preferably, in step 2), the ultrasonic dispersion conditions include: ultrasonic frequency of 25-30kHz, power density of 0.5W / cm 3 , time is 20-40min.
7. The preparation method according to any one of claims 3 to 6, characterized in that In step 2), the preparation method of the ZnMgAl-MOFs includes: a) dissolving zinc salt, magnesium salt and aluminum salt in a solvent to obtain a mixed solution, adding a ligand solution to the mixed solution, and performing a microwave solvothermal reaction to obtain a MOFs material; b) adding a surfactant during the first crystallization process of the MOFs material to continue the microwave solvothermal reaction to obtain ZnMgAl-MOFs; Preferably, in step a), the zinc salt is selected from one or two or more of zinc nitrate, zinc chloride and zinc sulfate, the magnesium salt is selected from one or two or more of magnesium nitrate, magnesium chloride and magnesium sulfate, and the aluminum salt is selected from one or two or more of aluminum nitrate, aluminum chloride and aluminum sulfate; The ligand solution is an ethanol solution of 2-methylimidazole and trimesic acid; More preferably, in step a), the molar ratio of the zinc salt, the magnesium salt and the aluminum salt is 1:0.5-2:0.5-2, wherein the zinc salt is calculated as zinc ion, the magnesium salt is calculated as magnesium ion, and the aluminum salt is calculated as aluminum ion; Further preferably, in step a), the microwave reaction conditions include: power of 800-1200w, temperature of 140-150°C, and time of 20-40min; More preferably, in step b), the surfactant is sodium dodecylbenzenesulfonate and / or cetyltrimethylammonium bromide; More preferably, the concentration of the surfactant is 0.01-0.05 mol / L; More preferably, in step b), the conditions of the microwave solvothermal reaction include: power of 800-1200W, temperature of 140-150°C, and time of 20-40min.
8. The preparation method according to any one of claims 3 to 7, characterized in that In step 3), the surfactant is sodium dodecylbenzenesulfonate and / or hexadecyltrimethylammonium bromide; Preferably, the concentration of the surfactant is 0.01-0.05 mol / L.
9. The preparation method according to any one of claims 3 to 8, characterized in that In step 3), the conditions of the microwave solvothermal reaction include: power of 800-1200W, temperature of 140-150°C, and time of 20-40min.
10. A downward-blowing water-cooled PE film, characterized in that: The downward-blowing water-cooled PE film comprises functional materials, PE resin and maleic anhydride-grafted PE; wherein the functional material is the downward-blowing water-cooled PE film functional material according to claim 1 or 2 or the downward-blowing water-cooled PE film functional material prepared by the preparation method according to any one of claims 3-9.